Fractal dimensions of chaotic at tractors for monsoon rainfall of meteorological sub-divisions of India (MAUSAM, 1997)
ABSTRACT .The correlation fractal dimension of strange at tractors of southwest monsoon rainfall of all the 35 Indian meteorological sub-divisions and India as a whole and nonh-east monsoon rainfall of 4 meteorological sub-divisions of peninsular India are estimated using the Grassberger and Procaccia algorithm (1983-). The fractal dimensions provide us the primary information on the number of parameters that are required to understand the dynamics underlying the monsoon dynamic system. The fractal dimensions varied between 2.9 and 7.1 and the saturation occurred between 14 and 21 ~ dimensions. In 5 sub-divisions the fractal dimension could not be determined.